A Study on Marketing Strategy of Selected Home Appliances in Kolkata - Ghosh, Chinmoy (International Research Journal of Management, IT & Social Sciences, 2016)
Now that is the era of marketing strategy based on that the reputed companies try to maintain their position in the market. We actually study the new pattern of marketing strategy which influences customers to buy a particular product. The study provide a new horizon of marketing strategy poke (shock-knock), based upon the Maslowâs highest need level self-actualization.